Exploration on the Influence of Oxidative Stress on the Progression of Age-related Degenerative Lesions - Yiwen Wang (International Journal of Public Health and Medical Research, 2026)
Research on how oxidative stress affects the development of age-related degenerative diseases. Rather than considering oxidative stress as an increase in free radicals, this paper now refers to it as a fluctuating disorder in redox homeostasis that involves reactive oxygen species, antioxidant defence, mitochondrial function, inflammatory amplification and damaged cell repair. Based on the classic theories of ageing and later review literature, this paper examines how oxidative stress contributes to the accumulation of molecular damage and promotes structural and functional deterioration in ageing tissues. Oxidative stress is also related to disease, and at the same time, it is a type of damage that occurs in blood vessels, nerves and metabolism. Therefore, it has been proposed that the development of degenerative changes in old age is the result of multiple interconnected redox, inflammatory and signalling pathways rather than single-cause damage to tissues.